Limites e possibilidades da educação musical inclusiva: as práticas de percussão para crianças e adolescentes com transtorno do espectro autista - Costa Neto, Ivo Pereira da (2022)
This work deals with the Limits and possibilities of Inclusive Music Education, considering the percussion practices for children and adolescents with Autistic Spectrum Disorder (ASD). The research problematic arose from the reflections about the activities developed in the workshops in the Atoque Social Percussion Project, Santa Maria - Rio Grande do Sul. The master's thesis is linked to the Education and Arts research line - LP4, of the Graduate Program in Education, from the Federal University of Santa Maria and to the research group NarraMus and has as general objective - To analyze the effects of the musical intervention of the percussion workshop, and the social and learning relationship of children and adolescents with Autistic Spectrum Disorder (ASD). ), contributing to their social inclusion. The research study methodology is qualitative. Data were collected through semi-structured interviews with parents and guardians, narratives that portray the importance of remembrance in rescuing life stories. The narratives became relevant to this research, because it instigated the educator the possibility of acting as an active protagonist narrator, writer of stories that are constituted from different training situations, portraying the importance of learning and joint reflection with their subjects of research, featuring an open and meaningful dialogue in the academic process. The research subjects consisted of the researcher himself and the relationship developed in the workshops of the Atoque Social Percussion Project with six children and adolescents aged 9 to 17 years diagnosed with ASD, as well as with the collaboration and participation of their respective guardians. . The theoretical framework was based on studies by authors of music education, inclusive music education, Autistic Spectrum Disorder and Social Project, such as - Souza (2008), Chiarelli and Barreto (2005), Brito (2003), among others. It was found that there are many challenges that are presented to improve the development and interaction of children and adolescents with Autism Spectrum Disorder. In the interviews collected with parents and guardians of students with the spectrum, there were many questions that were related to the percussion workshop and its collaborations in the lives of these subjects, issues that were only discovered after the reports of the guardians, who mentioned that in addition to The workshop contributes to an improvement in the development of the concentration of social relationships also helped in the coexistence of siblings in their family environment, in improving the quality of sleep of children after entering the workshop, helping to improve the speech and reading of one of the students and in overcoming the fears that accompanied him throughout his life. Therefore, these surveys confirm that music professionals, family members of children and adolescents with ASD, understand that music can be a form of treatment aid for these individuals, bringing benefits and a better quality of life for subjects with TEA and their families.